Социализация личности в условиях трансформации социокультурного пространства - Кокорина, Е.Г. (Культура народов Причерноморья, 2014)
В данной статье рассматриваются особенности развития и социализации личности под
воздействием различных факторов – как внутренних, так и внешних – в условиях социокультурных
трансформаций. В стабильные периоды мы говорим о поэтапном развитии личности. В условиях
переходного периода мы становимся свидетелями внезапных и часто неожиданных для большинства
изменений, которые в своей совокупности приводят к значительным переменам и обусловливают новую
специфику и темпы социализации личности. У статті, що пропонується, розглядаються особливості розвитку та соціалізації
особистості під впливом різних чинників – як внутрішніх, так і зовнішніх – в умовах соціокультурних
трансформацій. У стабільні періоди ми говоримо про поетапний розвиток особистості. В умовах
перехідного періоду ми стаємо свідками раптових і часто несподіваних для більшості змін, які у своїй
сукупності призводять до значних наслідків і обумовлюють нову специфіку й темпи соціалізації
особистості. The article is devoted to the peculiarities of personality development and socialization under the
influence of various factors in the conditions of socio-cultural transformation. In addition to regulatory,
mandatory crises, largely due to internal reasons, the person in the course of its development is also facing
changes in the external environment. In stable periods we're talking about the gradual development of the
personality. In the transitional period we are witnessing the sudden and often unexpected for most changes,
which cumulatively lead to significant change and determine new specificity and rate of socialization. People
are facing sudden it changes, which necessarily affect anyone who will be in their field, and entail the need for
additional socialization and adaptation. On the one hand, the crisis of identity that accompanies social
transformation is significantly traumatic for a person. On the other hand, transitional periods increase the
degree of freedom in which innovations occur at different levels of society.